Implementasi Therapy Community bagi Pemulihan Pecandu Narkoba di Yayasan Rehabilitasi Medan Plus Rantau Prapat - Nirwana Br Batubara; Rahmat Haikal; Wanda Afriani Ritonga; Firda Rani Harahap; Dodi Sutra Sitompul; Elida Hannum; Arifin Hidayat (JISPENDIORA Jurnal Ilmu Sosial Pendidikan Dan Humaniora, 2025)
This study aims to examine the implementation of the Therapeutic Community (TC) model in the rehabilitation process of drug addicts at Medan Plus Rehabilitation Foundation, Rantau Prapat. The research applied a descriptive qualitative approach with data collected through in-depth interviews, observation, and documentation. The findings indicate that the TC program is carried out in several phases: orientation, primary, re-entry, and aftercare. Clients are trained in discipline, building healthy social relationships, and strengthening self-control and motivation for a drug-free life. The TC method is proven effective in fostering behavioral change, increasing self-confidence, and reducing relapse tendencies. The challenges encountered include limited trained human resources, inadequate facilities, and initial client resistance to community-based routines.